Protection of Human Rights Victims of Sexual Violence through Maqâsid al-Sharî'ah: A Case in Batu City Indonesia - Miftahudin Azmi (Jurnal HAM, 2022)
Sexual violence can happen anywhere, and some perpetrators are usually related to the victim. A case of sexual violence occurred at Selamat Pagi Indonesia School in Batu city. The schoolmaster threatened the victim to comply with his wishes. A school environment, which should be a place to learn about science and ethics, has become a scene for sexual assault. This article aims to provide prevention and settlement alternatives for sexual violence through maqâsid al-sharî'ah methods. The data show that sexual violence at the school has occurred since 2009. This article includes empirical research using qualitative methods by describing and analyzing the data which is presented in descriptive text. The result of the research shows that the victims are incapable of fighting back due to manipulation in order to always be obedient and repay the perpetrators. The intimidation practice is in contrast to human rights and religious purposes, while the perpetrators exploit the power relation and manipulate religious narratives to commit the crime. Understanding religious purposes (maqasid alsharî'ah) provides essential tools to minimize human rights violations in the form of sexual violence. One is allowed to make prejudices and refuse to engage in an activity that may lead to sexual violence. The resistance corresponds with maqâsid al-sharî'ah which consists of safeguarding the soul, progeny, mind, religion, and wealth.